The pragmatic programmer : your journey to mastery - Thomas, David, 1956-; Hunt, Andrew, 1964- (Addison-Wesley, 2020)
"Straight from the trenches, The Pragmatic Programmer, 20th Anniversary Edition, cuts through the increasing specialization and technicalities of modern software development to examine the core process: transforming a requirement into working, maintainable code that delights users. Extensively updated with ten new sections and major revisions throughout, this edition covers topics ranging from career development to architectural techniques for keeping code flexible, adaptable, and reusable. The Pragmatic Programmer illustrates today's best practices and major pitfalls of many different aspects of software development. Whether you're a new coder, an experienced programmer, or a manager responsible for software projects, applying this guide's lessons will help you rapidly improve your productivity, quality, and job satisfaction"--
Keywords: programování; vývoj softwaru; software; programming; software development; příručky; handbooks and manuals